2020
DOI: 10.1016/j.jtbi.2019.110110
|View full text |Cite
|
Sign up to set email alerts
|

The generality of transient compartmentalization and its associated error thresholds

Abstract: Can prelife proceed without cell division? A recently proposed mechanism suggests that transient compartmentalization could have preceded cell division in prebiotic scenarios. Here, we study transient compartmentalization dynamics in the presence of mutations and noise in replication, as both can be detrimental the survival of compartments. Our study comprises situations where compartments contain uncoupled autocatalytic reactions feeding on a common resource, and systems based on RNA molecules copied by repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Through these processes, genetic molecules in each compartment can be randomly redistributed into new compartments, by which functional genetic molecules could be separated from parasitic molecules if the number of parasites is not large compared with the number of newly formed compartments. Previous studies that used water-in-oil emulsions or theoretical models demonstrated the sustained replication of genetic molecules with the appearance of parasites through all three processes: cycles of disruption and formation (Figure 3a) [14,[40][41][42], fusion and fission (Figure 3b) [13,15,20,43,44], and growth and division (Figure 3c) [29,[45][46][47] of compartments. caused by freezing and thawing (F-T) through day-night temperature cycling, could induce uptake of substrates.…”
Section: Compartments With Boundariesmentioning
confidence: 84%
“…Through these processes, genetic molecules in each compartment can be randomly redistributed into new compartments, by which functional genetic molecules could be separated from parasitic molecules if the number of parasites is not large compared with the number of newly formed compartments. Previous studies that used water-in-oil emulsions or theoretical models demonstrated the sustained replication of genetic molecules with the appearance of parasites through all three processes: cycles of disruption and formation (Figure 3a) [14,[40][41][42], fusion and fission (Figure 3b) [13,15,20,43,44], and growth and division (Figure 3c) [29,[45][46][47] of compartments. caused by freezing and thawing (F-T) through day-night temperature cycling, could induce uptake of substrates.…”
Section: Compartments With Boundariesmentioning
confidence: 84%
“…For this, catalysts within autocatalytic networks should exhibit high enough specificity toward the reactions of the network to overcome degradation and losses due to side reactions. Given an autocatalytic set of reactions, each catalyzed with a specificity (where , disappearance can be avoided, provided , thereupon revealing a “decay threshold” ( Szathmáry, 2006 ; Vasas et al., 2012 ; Blokhuis et al, 2020a ). Furthermore, for survival to be possible, the concentration of feedstock compounds must stay above a specific value most of the time.…”
Section: The Diversity Of Thresholds In Origin Of Lifementioning
confidence: 99%
“…, thereupon revealing a ''decay threshold'' (Szathmá ry, 2006;Vasas et al, 2012;Blokhuis et al, 2020a). Furthermore, for survival to be possible, the concentration of feedstock compounds must stay above a specific value most of the time.…”
Section: The Diversity Of Thresholds In Origin Of Lifementioning
confidence: 99%
“…Inspired by the work of S. Matsumura, we recently explored general scenarios of transient compartmentalization that are also able to maintain information in replicating systems [9,10]. We proposed a transient compartmentalization dynamics with no cell division, which should be achievable when only prebiotic chemistry is available.…”
Section: Introductionmentioning
confidence: 99%